In vitro regeneration of soybean (a review) - E. S. Bespalova; K. M. Ershova; Yu. V. Ukhatova (Труды по прикладной ботанике, генетике и селекции)
This is an overview of contemporary published works dedicated to the ability of soybean plants to regenerate in vitro and the techniques to achieve high regeneration rates, which is a necessary condition for the inclusion of soybean genotypes in genome editing programs. The main factors that determine the regenerative capacity of explants from various soybean accessions are considered. The greatest effect on the efficiency of regeneration is exerted by the conditions of in vitro culture initiation, type of explant, composition of the nutrient medium, shelf life of seeds, and genotypic characteristics of soybean accessions.